Morphological and anatomical assessment of the nasopalatine canal in edentulous patients using cone beam computed tomography - Talebian, Mahtab; Etemad, Shahab; Abbasi Seimareh, Khalil (Revista Publicando, 2018)
Nasopalatine canal (NPC) is one of the most important anatomical structures in the anterior maxilla; therefore, it is necessary to advance our knowledge about its features for dental implant treatment in this region. The aim of the current study was to investigate the morphological and anatomical variations of the NPC using cone beam computed tomography (CBCT) in a subset of Iranian maxillary edentulous patients. Material and methods: The characteristics of the NPC were examined on CBCT images of 48 (29 males and 19 females with a mean age of 53.04 years) edentulous patients. The sagittal sections of CBCT images were used to examine the shape (funnel- like, cylindrical, hourglass- like and banana- like) and dimensions of the NPC canal (the length of the NPC, the diameter of the foramina of Stenson (FS) and incisive foramen (IF)) of the NPC) and buccal bone wall. The shape of the incisive foramen was assessed on axial sections of CBCT images and were categorized to round, oval, heart- shaped and lobular. Results: The mean diameter of FS and IF were 3.60 1.44 mm and 6.78 2.56 mm respectively. The mean length of the NPC was 12.70 2.22 mm and the width of buccal bone plate increased from the crestal to apical level. Cylindrical (50%) and round (58.34) were the most prevalent shapes of the NPC and IF respectively. The age and gender of patients did not have any significant effect on the shape and dimensions of the NPC (p>0.05).Discussion: The results of this study showed that morphological and dimensional characteristics of the NPC in edentulous patients are not affected by age and gender. However, further research is needed to confirm this finding among Iranian population.